How face consciousness reverse pro-self-behavior? A study on ecological consumption from the perspective of social value orientation. Issue 1 (3rd September 2018) - Shi, Zhuomin; Wu, Lufang; Kuang, Zaoying
Abstract : Purpose: The purpose of this paper is to focus on ecological consumption and test the effect of social value orientation on ecological consumption. What is more, this paper explores how Chinese consumers choose between prosocial and non-prosocial products under the influence of Chinese face culture. Design/methodology/approach: The authors assume that social value orientation will change individual's ecological consumption through the in-group identification, and simultaneously predict that the influence in pro-self and pro-social consumer groups will vary. Furthermore, Chinese face consciousness will moderate the relationship between ecological consumption and social value orientation. Online research and intercept survey are employed to collect data. In total, 600 questionnaires were distributed. Findings: The results indicate that pro-social individuals prefer sustainable consumption than pro-self-individuals, and in-group identification mediates the effect of social value orientation on ecological consumption. Interestingly, pro-self-individuals' behaviors have changed dramatically by the influence of face consciousness. Originality/value: The authors discovered that social value orientation has a deep impact on ecological consumption through in-group identification. The authors tested and verified the dominance of Chinese face culture. Besides, four key elements of China's "face" construct are proposed, namely, holism, synergy, synchronicity and dynamics, which enlarge the horizon of the theory of face.